Child Development in a Region of Madagascar With High Child Undernutrition. (7th June 2021) - Rakotomanana, Hasina; Thomas, David; Fawbush, Fanjaniaina; Hildebrand, Deana; Gates, Gail; Komakech, Joel; Walters, Christine; Stoecker, Barbara
Abstract: Objectives: The Vakinankaratra region of Madagascar has a high burden of child undernutrition, a strong risk factor for poor child development. The purpose of this preliminary study was to assess the household stimulation environment and to evaluate the development of 11 to 13 month-old toddlers from this agriculturally-productive area with some of the highest young-child stunting rates in the world. Methods: Stunting (length-for-age z-score < -2) and underweight (weight-for-age z-score < -2) were determined using the 2006 WHO growth standards. Household stimulation environment was evaluated using the Family Care Indicators scales. The Bayley Scales of Infant and Toddler Development III were used to directly evaluate development of 36 toddlers (mean age 11.9 mo). Age-appropriate, increasingly difficult tasks are provided by the Bayley Scales to assess cognition, language, and motor skills. Socioemotional development also was evaluated using a questionnaire individually administered to the primary caregivers of 76 toddlers (mean age 11.7 mo). Results: More than two-thirds (69%) of young children in the sample were stunted and 11% were underweight. Most mothers used household objects (75%) and materials from outside the house (71%) as children's toys such as makeshift balls made of plastic wraps. Common adult-infant interactions were talking and playing. In most households, adults told stories or read a book to children only once a week at most. However, these interactions were limited by other responsibilities of the parents. Scoring of the Bayley scales is adjusted to provide composite scores with a mean of 100 for each domain for each age group. Below average scores were determined in our sample as follows: cognitive [mean (SD): 60 (10.3)], motor [61.9 (13.4)], language [62 (13.2)], and socioemotional [85.1 (17.9]). Although in this small sample there were no statistical differences based on nutritional status, development scores for fine motor, cognitive, and receptive and expressive language were correlated [0.4 < r < 0.7, p < 0.05 ]. Conclusions: The very high stunting rates and very low cognitive, motor, language, and socioemotional scores of young children in the Vakinankaratra region require urgent attention. Funding Sources: This study was funded by the Marilynn Thoma Chair in Human Sciences at Oklahoma State University.